Pengaruh Propolis Terhadap Il-6 Pada Diabetes Melitus Tipe 2: A Literature Review - Nazula Rahma Shafriani (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Type-2 diabetes is a metabolic disease characterized by an increase in blood sugar levels due to decreased insulin secretion by pancreatic beta cells, or inappropriate insulin action. The pathophysiology of type-2 diabetes is related to inflammatory mechanisms caused by an increase in proinflammatory cytokines such as IL-6. Propolis has an anti-inflammatory role that can influence type 2 diabetes. To determine the effect of propolis as an anti-inflammatory to the IL-6 cytokines in type 2 Diabetes Mellitus A Literature review by searching electronic databases on Pubmed, ProQuest, and Google Scholar with the keywords "propolis or bee propolis and IL-6 levels or interleukin-6 levels and diabetes type-2 or type-2 diabetes" published in 2010-2020. Based on the search results, 9 journals were found. These articles consist of 5 experimental articles and 4 RCT articles. Five databases reported a decrease in IL-6 levels and three journals stated that there was an increase in IL-6 levels in the type-2 diabetes group after being given propolis. One journal reported no significant difference. Variations in propolis administration and time in IL-6 measurements affected the tendency to decrease IL-6 levels in type 2 diabetes patients. The active components in propolis were influenced by differences in plant resources, collection season, bee species, and solvents used in the extraction. IL-6 levels in the type-2 diabetes group tended to decrease after propolis administration compared to the type-2 diabetes group without propolis administration. IL-6 levels in the type-2 diabetes group increased after propolis administration because IL-6 helps improve chronic inflammation associated with type-2 diabetes.